2010
DOI: 10.1037/a0019137
|View full text |Cite
|
Sign up to set email alerts
|

Helping students soar to success on computers: An investigation of the SOAR study method for computer-based learning.

Abstract: This study used self-report and observation techniques to investigate how students study computer-based materials. In addition, it examined if a study method called SOAR can facilitate computer-based learning. SOAR is an acronym that stands for the method's 4 theoretically driven and empirically supported components: select (S), organize (O), associate (A), and regulate (R). There were 2 experiments. In Experiment 1, 114 undergraduates completed a questionnaire about how they study computer-based materials. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 80 publications
(104 reference statements)
2
25
0
Order By: Relevance
“…In addition to their links to academic motivation and achievement in a variety of classroom‐based settings (Albaili, ), cognitive strategies provide direct academic benefits in online settings. For instance, the use of effective cognitive strategies when studying computer‐based materials has been shown to relate to high performance on comprehension and recall tests (Jairam & Kiewra, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In addition to their links to academic motivation and achievement in a variety of classroom‐based settings (Albaili, ), cognitive strategies provide direct academic benefits in online settings. For instance, the use of effective cognitive strategies when studying computer‐based materials has been shown to relate to high performance on comprehension and recall tests (Jairam & Kiewra, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…A related form of mapping is to create or fill in a graphic organizer or matrix to spatially represent one's notes, such as to represent a compare-and-contrast structure (e.g., Kiewra et al, 1991;Robinson & Kiewra, 1995). For example, in a study by Jairam and Kiewra (2010), college students read a text lesson presented on a computer about different types of wildcats. Students were either asked to take linear notes using a window on the screen or to fill in an onscreen matrix that helped students organize different characteristics attributed to each type of wildcat.…”
Section: Mapping Learning By Mapping Involves Creating An Abstract Smentioning
confidence: 99%
“…The importance of metacognitive strategies is also evident in the digital reading environment (Akyel & Erçetin, 2009;Stadtler & Bromme, 2007). For example, Jairam and Kiewra (2010) found that students who used the full SOAR (select, organize, associate and regulate) strategies had better online reading scores than those in the control or partialstrategy groups. In addition, skilled readers performed better in monitoring their comprehension of questions and information searching during online task-oriented reading assignments (Vidal-Abarca, Mañá, & Gil, 2010).…”
Section: Metacognitive Strategies and Reading Literacymentioning
confidence: 99%